The Biology and Natural Control of the Scale Drepanococcus chiton (Green)(Homoptera : Coccidae), a Minor Pest of Carambola in Malaysia - Ibrahim, Abdul Ghani (Universiti Putra Malaysia Press, 1994)
The scale, Drepanococcus chiton (Green) (Homoptera: Coccidae) is a potential pest of carambola, variety Bl0 Averrhoa carambola. The insects caused drying of shoots and flower stalks. The regimental spraying of insecticides against the fruit flies, Bactrocera dorsalis, possibly gave rise to a build-up of the scale populations in a carambola orchard at Sungai Long, Ulu Langat, Selangor. The development of eggs to adult maturity at 28± 1.5 °C was 49.9± 1.06 days. A female scale could produce an average of 1081.9± 256.0 eggs with 97.9% viability. However, only 2.5% of these eggs reached adult maturity in the field. Field observation showed that the scales are being parasitised by an egg-parasitoid, Eunotus sp. (Hymenoptera: Pteromalidae). The average monthly parasitisation by Eunotus sp. from August 1992 to February 1993 was 40.6%. The parasitic larva was capable of destroying 93.2% of the scale's eggs during its larval development. The sex ratio of male to female parasitoid was 1 : 1.